DETERMINAN KEJADIAN DISMENORE PADA REMAJA PUTRI DI SMA NEGERI 9 KOTA DEPOK - Farah Nabilla Azzura (2023)
Teenagers will experience biological changes such as menstruation that occurs in young women, during menstruation some of them also often experience menstrual pain in the lower abdomen. The high prevalence of dysmenorrhea in Indonesia reaches 90%. Several factors that have been analyzed as a risk factor for dysmenorrhea are knowledge of the range of dysmenorrhea, calcium intake, magnesium intake, zinc intake. The purpose of this study was to determine the factors associated with the incidence of dysmenorrhea in young women at SMA Negeri 9 Depok City. The study used a cross-sectional design with stratified random sampling used as a sample. The population in this study were class X and XI as many as 81 students. Frequency analysis showed that the majority of respondents experienced dysmenorrhea of 70.4%, low knowledge of 86.4%, insufficient intake of calcium 66.6%, insufficient intake of magnesium 56.8%, insufficient intake of zinc 84%, adequate intake of Fe 69.1%, light physical activity 79%, stress 92.6%. Chi-square analysis found a relationship (p<0.05) between knowledge, calcium, magnesium, zinc, physical activity and the incidence of dysmenorrhea and there was no relationship between stress and the incidence of dysmenorrhea. Siwi who have low knowledge are at risk of experiencing dysmenorrhea 15.784 times compared to female students who have good knowledge (p=0.012). Young women need to increase their knowledge about dysmenorrhea and pay more attention to good and adequate nutrition.